Extraction of Chemical Warfare Agents from Soils: Case Study on O-ethyl S-2-(diisopropylamino)ethyl methylphosphonothiolate (VX) - Zuas, Oman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
Extraction of chemical warfare agents, O-ethyl S-2-(diisopropylamino)ethyl methylphosphonothiolate (VX) in soilsample has been carried out. The extraction was performed using six different solvents including 1% TEA/MeOH,1% NH4OH/MeOH, water pH 2 at the ambient temperature , water pH 2 at temperature 4 0C, water pH 7 at ambienttemperature, and water pH 7 at temperature 4 0C. Percent recovery of VX in soil samples was quantitativelydetermined by mean LC-MS using selected reaction monitoring (SRM). Among the solvents used, water pH 2 attemperature 40C gave the best extraction capability that was indicated by the highest percent recovery of VXobtained. Storing effect of spiked samples was also investigated by extracting the samples containing VX usingwater at pH 2/40C and the degradation product was then identified using multiple reaction monitoring (MRM). Fromthe study, two degradation products were identified as Bis[2-(diisopropylamino)ethyl]disulphide and ethylmethylphosphonate.